Towards a Cognitive-Linguistic Turn in CLIL: Unfolding Integration - Margit Reitbauer; Ulla Fürstenberg; Petra Kletzenbauer; Karoline Marko (Universidad de La Sabana, 2018)
The aim of this paper is to unfold the process of integration in CLIL by describing the role of the cognitive processes involved in the construction of knowledge. While there has been extensive research of various aspects of CLIL, the actual process of integration of content and language has largely been neglected. Therefore, this paper argues that the role of language in building knowledge has to be stressed further and made transparent to CLIL practitioners, particularly in "hard" versions of CLIL. Raising teachers' awareness of the epistemic function of language and drawing their attention to the human cognitive architecture can help them achieve a higher level of understanding of the process of integration of content and language. Using the example of a task taken from a training course for CLIL teachers, this paper describes how a focus on the cognitive architecture of learners can improve the integration of content and language in CLIL.